2015
DOI: 10.1371/journal.pone.0135273
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Evaluation of the Upper Airway Morphological Changes in Growing Patients with Skeletal Class III Malocclusion Treated by Protraction Headgear and Rapid Palatal Expansion: A Comparative Research

Abstract: ObjectiveThe aim of this study was to evaluate the morphological changes of upper airway after protraction headgear and rapid maxillary expansion (PE) treatment in growing patients with Class III malocclusion and maxillary skeletal deficiency compared with untreated Class III patients by cone-beam computed tomography (CBCT).MethodsThirty growing patients who have completed PE therapy were included in PE group. The control group (n = 30) was selected from the growing untreated patients with the same diagnosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 42 publications
1
28
1
Order By: Relevance
“…[1][2][3][4][5] Previous studies on airway morphology of patients with Class III malocclusion have been focused on the change of airway dimension after treatment with protraction headgear, 6 mandibular setback, 7,8,9 or bimaxillary surgery. 10 Ritcher et al 11 reported two cases of obstructive sleep apnea syndrome found in asymmetrical patients, indicating that upper airway obstruction could exist in patients with mandibular asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Previous studies on airway morphology of patients with Class III malocclusion have been focused on the change of airway dimension after treatment with protraction headgear, 6 mandibular setback, 7,8,9 or bimaxillary surgery. 10 Ritcher et al 11 reported two cases of obstructive sleep apnea syndrome found in asymmetrical patients, indicating that upper airway obstruction could exist in patients with mandibular asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of RME or FM on the pharyngeal airway have been repeatedly investigated using various methods, such as cephalometric radiography, computed tomography (CT) and cone beam CT (CBCT), to measure the changes in airway dimensions. However, the study outcomes were inconsistent . Statistically significant dimensional changes in the pharyngeal or nasopharyngeal airway were observed after RME and/or FM treatment in some studies, whereas no significant or limited changes were observed in others .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, RME and FM were found to exert secondary treatment effects by increasing the pharyngeal airway dimension. However, several studies used only FM, some performed only RME, and other studies conducted FM in combination with RME …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated that orthodontic treatment causes morphological or functional changes of upper airway34. Therefore, detailed evaluation of the upper airway is essential for orthodontic diagnosis and planning.…”
mentioning
confidence: 99%